Senescence Is Associated With Elevated Intracellular Resting [Ca2 +] in Mice Skeletal Muscle Fibers. An in vivo Study - Mijares, Alfredo; Allen, Paul D.; Lopez, Jose R. (Frontiers in Physiology, 2021)
Aging causes skeletal muscles to become atrophied, weak, and easily fatigued. Here we have tested the hypothesis that normal aging in skeletal muscle cells is associated with Ca2+ intracellular dyshomeostasis and oxidative stress. Intracellular Ca2+ concentration ([Ca2+]i), resting intracellular Na+ concentration ([Na+]i) and reactive oxygen species (ROS) production were measured in vivo (superficial gastrocnemius fibers) using double-barreled ion-selective microelectrodes, and in vitro (isolated single flexor digitorum brevis (FDB) fibers) using fluorescent ROS sensor CM-H2DCFDA in young (3 months of age), middle-aged (12 months of age), and aged (24 months of age) mice. We found an age-related increase in [Ca2+]i from 121±4 nM in young muscle cells to 255±36 nM in middle-aged and to 409±25 nM in aged cells. [Na+]i also showed an age-dependent elevation, increasing from 8±0.5 mM in young muscle fibers, to 12±1 mM in middle-aged and to 17±1 mM in aged muscle fibers. Using the ROS sensor CM-H2DCFDA we found significantly increased basal ROS production. We administered Flufenamic acid (FFA), a non-steroidal anti-inflammatory (NSAID), and a non-selective blocker of TRPCs, 12.5 mg/kg intraperitoneally daily for 4 weeks. FFA treatment reduced DCF fluorescence levels in middle-aged and aged muscle fibers and this decrease iwas associated with a significant reduction of [Ca2+]i and [Na+]i. In addition, FFA treatment also reduced the age associated increases in plasma interleukin 6 (IL-6) and tumor necrosis factor-alpha (TNF-α) concentrations which were elevated in 12 and 24-mo old mice compared to young mice and decreases age related muscle damaged as indicated by a reduction in serum creatine kinase (CK) activity. Our data provide the first direct demonstration that normal aging is associated with a significant elevation [Ca2+]i, [Na+]i, and intracellular ROS production in skeletal muscle fibers. Furthermore, the fact that FFA reduced the intracellular [Ca2+], [Na+], and ROS overload as well as the elevated IL6, TNF-α and CK levels, led us to suggest that its pharmacological effect may be related to its action as TRPC channel blocker and as an NSAID.